3-year experience of hyperthermic intravesical chemotherapy use in patients with high risk non-muscular-invasive bladder cancer - R.S. Chystiakov; F.I. Kostyev; O.V. Bondar; V.V. Lysenko; V.O. Varbanets (Medičnì Perspektivi)
Cur   rently, the search for additional organ-sparing methods of intravesical therapy for non-muscular-invasive bladder cancer (NMIBC) is actively continuing, which could become an effective alternative to standard treatment using the Bacillus Calmette-Guérin (BCG) vaccine. The aim of this work was to analyze the safety profile and long-term results of treatment of patients with the high-risk non-muscular-invasive bladder cancer who received adjuvant intravesical chemotherapy using the Combat BRS HIVEC® device for local hyperthermia (HIVEC® therapy group; n=53) in comparison with patients who received adjuvant therapy after transurethral resection of bladder performed with the Bacillus Calmette-Guérin vaccine (BCG therapy group; n=54). As a result, the median follow-up was 30 months (range 7-36). According to Common Terminology Criteria for Adverse Events (CTCAE) v 5.0, the most relevant side effects in HIVEC®/BCG therapy groups were adverse events grade 1-2: fever – 1%/8%; dysuria – 9%/13%; bladder spasms – 7%/12%; hematuria – 3%/4% and urinary tract infection – 3%/10%. Tumor recurrence was reported in 23 patients receiving intravesical BCG therapy and in 10 patients receiving intravesical hyperthermic chemotherapy (42.6% versus 18.9%, p=0.008). Tumor progression was recorded in 11 patients receiving intravesical BCG therapy and in 4 patients receiving intravesical hyperthermic chemotherapy (20.4% versus 7.5%, p=0.046). The study allows us to conclude that the method of hyperthermic intravesical chemotherapy has a better safety profile compared to intravesical Bacillus Calmette–Guérin vaccine therapy, while such indicators of oncological efficacy as 3-year recurrence-free survival and the incidence of progression were better in the HIVEC® therapy group.